Meningkatnya Risiko Disabilitas Pada Penduduk Dengan Penyakit Tidak Menular: Analisa Lanjut Riskesdas 2013 - Isfandari Siti; betty roosihermiatie (Pusat Penelitian dan Pengembangan Humaniora dan Manajemen Kesehatan, 2018)
Intersectoral approach is essential to develop program for people with disability in Indonesia. Coordination across ministries are necessary to manage this issue. The planning, provision and monitoring of medical and support services as well as program for population groups with disability may require assessment. Purpose of this study is to assess disability in Indonesia. Methods: performing analysis of disability data from 2013 Indonesian Household Health Survey known as Riskesdas. Level of disability obtained from two main population groups: those with and without non communicable disease (NCD). They then divided by age. The World Health Organization Disability Assessment Schedule II (WHODASII) was used to measure disability. Results: contribution of NCD on disability is obvious among older age indicated by higher proportion of disability with NCD. While risk of disability among younger age is unclear, since disability with NCDproportion is lower than disability without NCD. Probably risk of disability among younger age is other than NCD. None of the groups had members with extreme disability on their global WHO-DASII scores. The analysis identifi es target groups for each stakeholder to develop program for people with disability to reach their maximum potential. Abstrak Penanganan penduduk dengan disabilitas membutuhkan keterlibatan lintas kementerian. Diperlukan informasi besar masalah penduduk dengan disabilitas di Indonesia. Analisa bertujuan mengetahui besaran masalah. Metode: analisa deskriptif univariat dan bivariat data disabilitas Riskesdas 2013 untuk memperoleh Informasi disabilitas seluruh penduduk. Selanjutnya dilakukan analisa besaran disabilitas pada penduduk dengan dan tanpa Penyakit Tidak Menular (PTM). Kelompok ini kemudian digolongkan menurut umur. Instrumen The World Health Organization Disability Assessment Schedule II (WHO-DASII) digunakan untuk mengukur disabilitas. Hasil: 18% penduduk Indonesia mengalami disabilitas. Informasi lebih rinci 8,2% mengalami kesulitan ringan, 6,8% kesulitan sedang dan 3% kesulitan berat. Kontribusi PTM terhadap disabilitas terlihat jelas pada kelompok usia 45 tahun atau lebih ditunjukkan dengan lebih tingginya proporsi disabilitas dengan PTM. Sedangkan risiko disabilitas pada kelompok usia sebelum 45 tahun bukan PTM, karena proporsidisabilitas dengan PTM lebih rendah.